A review on the pharmacological effects of hormonal and antidiabetic drugs in the treatment of Polycystic Ovary Syndrome - Biswas, Sraboni (Brac University, 2020)
This thesis is submitted in partial fulfilment of the requirements for the degree of Bachelor of Pharmacy, 2019.